Perceived barriers to participation in physical activity among public sector employees at Jabatan Kerja Raya in Kuala Lumpur - Mohd Sam, Ahmad Lutfi; Zid, Azlina; Dzoolkarnain, Hasyyati Husna; Rozaidi, Nur Adliana; Abdul Rahim, Siti Aishah (Faculty of Sports Science and Recreation, 2024)
Physical activity is crucial for maintaining health and preventing chronic diseases. However, many people encounter perceived barriers that prevent them from participating in physical activity, resulting in low participation. This study aimed to investigate the perceived barriers to participation in physical activity among Jabatan Kerja Raya (JKR) employees in Kuala Lumpur. For the study, a questionnaire was used to collect data, which was then analysed using descriptive statistics and a non-parametric test, the Mann-Whitney U test. A total of 312 participants from the JKR head office in Kuala Lumpur were selected for this study. The participants were divided into two groups based on Gender: male (n=127) and female (n=185). Demographic data and information on external and internal barriers to physical activity were collected. The analysis revealed no significant differences between genders regarding perceived barriers to participation in physical activity (p > 0.05). Respondents of both genders reported comparable internal and external barriers to physical activity. To better promote health and well-being in the public sector and beyond, it may be helpful to understand both the internal and external factors that can improve participation in physical activity.